Three-dimensional periodontal investigations using a prototype handheld ultrasound scanner with spatial positioning reading sensor. - Chifor, Radu; Mengxun Li; Kim-Cuong T. Nguyen; Arsenescu, Tudor; Chifor, Ioana; Badea, Alexandru F.; Badea, Mindra E.; Hotoleanu, Mircea; Major, Paul W.; Le, Lawrence H.; Li, Mengxun; Nguyen, Kim-Cuong T; et al. (Medical Ultrasonography, 2021)
Aim: To demonstrate the feasibility of the 3D ultrasound periodontal tissue reconstruction of the lateral area of a porcine mandible using standard 2D ultrasound equipment and spatial positioning reading sensors.Material and Method: Periodontal 3D reconstructions were performed using a free-hand prototype based on a 2D US scanner and a spatial positioning reading sensor. For automated data processing, deep learning algorithms were implemented and trained using semi-automatically seg-mented images by highly specialized imaging professionals.Results: US probe movement analysis showed that non-parallel 2D frames were acquired during the scanning procedure. Comparing 3 different 3D periodontal reconstructions of the same porcine mandible, the accuracy ranged between 0.179 mm and 0.235 mm.Conclusion: The present study demonstrated the diagnostic potential of 3D reconstruction using a free-hand 2D US scanner with spatial positioning readings. The use of auto-mated data processing with deep learning algorithms makes the process practical in the clinical environment for assessment of periodontal soft tissues.